Social Arts Practices: Knowledge within the Field of Social Work and In-Between Fields - Toleikytė, Uršulė; Šarūnas, Tadas (Socialinė teorija, empirija, politika ir praktika, 2025)
The production of knowledge in the realm of social arts practices involves various disciplines. The discourse of these practice is polyphonic and multi-layered. Notably, research on social arts within the scope of social work has been expanding. Yet, the field of social work remains differently defined, with divergent definitions provided by researchers and practitioners. As a result, the discourse regarding the intersection of social arts and social work research is scattered and encompasses a range of knowledge, often loosely interconnected. Some researchers are concentrated on delineate the field of social work, while others – in between fields. However, existing research lacks a profound sociological analysis. Such an analysis could provide insights into how the knowledge of social arts practices is shaped within the context of social work. This raises questions about the role of social arts practices in social work research, how they are conceptualised and the significance of this knowledge in enhancing our comprehension of these practices. Consequently, this study aims is to bridge these knowledge gaps and reflect further constructive path for future research into social arts practices. In this literature analysis of social work research related to social arts we will adopt P. Bourdieu field theory approach.
Keywords: social arts practises; social work; discourse; Pierre Bourdieu; the field